Carbon dots versus nano-carbon/organic hybrids – dramatically different behaviors in fluorescence sensing of metal cations with structural and mechanistic implications. Issue 8 (10th March 2021) - Wang, Ping; Meziani, Mohammed J.; Fu, Yingqiang; Bunker, Christopher E.; Hou, Xiaofang; Yang, Liju; Msellek, Hind; Zaharias, Melina; Darby, Jasmine P.; Sun, Ya-Ping
Abstract : Carbon dots of surface-functionalized small carbon nanoparticles are dramatically different from fluorescent samples from thermal carbonization of organic precursors in their fluorescence quenching-based sensing of copper cations in solution. Abstract : Carbon dots (CDots) are defined as surface-passivated small carbon nanoparticles, with the effective passivation generally achieved by organic functionalization. Photoexcited CDots are both potent electron donors and acceptors, and their characteristic bright and colorful fluorescence emissions make them excellent fluorescence sensors for organic analytes and metal ions. For the latter extraordinarily low detection limits based on extremely efficient quenching of fluorescence intensities by the targeted metal cations have been observed and reported in the literature. However, all of the dot samples in those reported studies were made from "one-pot" carbonization of organic precursors mostly under rather mild processing conditions, unlikely to be sufficient for the required level of carbonization. Those dot samples should therefore be more appropriately considered as "nano-carbon/organic hybrids", characterized structurally as being highly porous and spongy, which must be playing a dominating role in the reported sensing results. In this study, we compared the dot samples from carbonization syntheses under similarly mild and also more aggressive processing conditions with the classically defined and structured CDots for the fluorescence sensing of copper(ii ) cations in aqueous solutions. The observed dramatic decoupling between quenching results for fluorescence intensities and lifetimes of the carbonization samples, with the former being extraordinary and the latter within the diffusion controlled limit, suggested that the quenching of fluorescence intensities was greatly affected by the higher local quencher concentrations than the bulk associated with the porous and spongy sample structures, especially for the sample from carbonization under too mild processing conditions. The major differences between the classical CDots and the nano-carbon/organic hybrids are highlighted, and the tradeoffs between sensitivity and accuracy or reproducibility in the use of the latter for fluorescence sensing are discussed.